Pemanfaatan Trello API Dalam Perancangan Sistem Informasi Project Monitoring Berbasis Web (Studi Kasus : Cahaya Kreatif Undangan Sidoarjo): Aisyah Jihan Marcha Farah Fikriyyah, Widhy Hayuhardhika Nugraha Putra, Buce Trias Hanggara - Aisyah Jihan Marcha Farah Fikriyyah; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Cahaya Kreatif is a printing company that specializes in invitations and non-invitation printing and has worked with a variety of Micro, Small, and Medium Businesses (MSMEs). In company processes, manual methods are also used in various printing ventures. This has several drawbacks, including data errors caused by human error and the need for more time estimation. Furthermore, tracking business processes in different projects is still done by manually entering project progress data into Microsoft Office Excel. Due to the urgency of this issue, a web-based framework to manage projects that use the Trello API is required to make it easier for users to track and monitor tasks is required. Due to the urgency of this problem, a web-based framework to manage projects that use the Trello API is needed to make it easier for users to track and monitor task progress. This system has three user roles: project managers who track and assign tasks, admins who enter project ordering data, and employees who update task progress. The study yielded 46 functional requirements and 1 non-functional requirement, which were modeled using 46 use cases, operation diagrams, sequence diagrams, interface design, and system design developed with the Laravel 7 framework and MySQL database using the Trello API. The results of the usability testing are 89.2 (acceptable) and the results of the usability testing are 89.2 (acceptable). The usability testing results are 89.2 (acceptable), and the prototype testing results are as predicted by the company.